solvedB33

# solvedB33 - S 33.1(P 4.4(i H(z = 1 z^-1*z^-2 z^-3(ii...

This preview shows pages 1–2. Sign up to view the full content.

Sheet1 Page 1 S 33.1 (P 4.4) ______________ (i) H(z) = 1 - z^(-1} - *z^(-2) + z^(-3) (ii) H(exp(j*omega)) = 1 - exp(-j*omega) - exp(-j*2*omega) + exp(-j*3*omega) = exp(-j*3*omega/2). .. *(exp(j*3*omega/2) - exp(j*omega/2) - exp(-j*omega/2) + exp(-j*3*omega/2)) = exp(-j*3*omega/2)*(2*cos(3*omega/2)-2*cos(omega/2)) Thus |H(exp(j*omega)| = |2*cos(3*omega/2)-2*cos(omega/2)| and |H(exp(j*omega)|^2 = (2*cos(3*omega/2)-2*cos(omega/2))^2 (Note: An alternative expression for |H(exp(j*omega)|^2 is found by expanding H(exp(j*omega))*H(exp(-j*omega)) ) To plot |H(exp(j*omega)|: h = [1 -1 -1 1] f = (0:511)/512 H = fft(h,512) plot(f,abs(H)), title('Amplitude Response'), xlabel('\Omega/2\pi') p (iii) x[n] = 1 = exp(j*0*n) y[n] = H(exp(j*0)*x[n] = 0 x[n] = (-1)^n = exp(j*pi*n) y[n] = H(exp(j*pi))*x[n] = 0 x[n] = exp(j*pi*n/4) y[n] = H(exp(j*pi/4))*x[n] = (1 - exp(-j*pi/4) - exp(-j*2*pi/4) + exp(-j*3*pi/4))*x[n] = (-sqrt(2)+1+j)*exp(j*pi*n/4) x[n] = cos(pi*n/4+q) y[n] = |H(exp(j*pi/4))| * cos((pi*n/4) + q + angle(H(exp(j*pi/4)))

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 03/21/2010 for the course ENEE 241 taught by Professor Staff during the Spring '08 term at Maryland.

### Page1 / 6

solvedB33 - S 33.1(P 4.4(i H(z = 1 z^-1*z^-2 z^-3(ii...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online